Faktor - Faktor yang Berhubungan dengan Pemanfaatan Posyandu Lansia di Wilayah Kerja UPT Puskesmas Noemoke Tahun 2024 - Vienelda Selan; Rina Waty Sirait; Masrida Sinaga; Serlie K. A. Littik (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Elderly Posyandu is a community-based health service that emphasizes promotive and preventive care for older adults. However, its utilization remains low in some areas. According to data from Noemuke Health Center, the attendance rate at Elderly Posyandu was 60% in 2021, increased to 70% in 2022, but sharply declined to 40% in 2023, falling far below the minimum service standard of 80%. This study aims to identify the factors associated with the utilization of Elderly Posyandu in the working area of Noemuke Health Center in 2024. This is a quantitative study using an analytical survey with a cross-sectional design. A total of 96 respondents were selected through simple random sampling from a population of 5,023 elderly individuals. Data were collected using structured questionnaires and analyzed with univariate and bivariate analysis using the chi-square test at a significance level of 0.05. The univariate analysis showed that most respondents had low knowledge (57.3%), negative attitudes (59.4%), lacked family support (58.3%), and lived far from the Posyandu (69.8%). The bivariate analysis found significant relationships between knowledge, attitude, family support, and distance to services with the utilization of Elderly Posyandu (p < 0.05). It is recommended that health centers improve regular education and outreach to both the elderly and their families, especially in remote areas. Family involvement and community engagement are also crucial to enhance participation. Further research should explore other potential factors such as socioeconomic status and the role of community leaders in influencing the utilization of Elderly Posyandu.